The influence of competition day loads on the metabolic and immune response of Olympic female beach volleyball athletes: A sportomics analysis - Muniz-Santos, R.; Bassini, A.; Alexandre, P. C. B.; Jurisica, I.; Chandran, V.; Cameron, L. C. (Nutrients, 2025)
Background: Beach volleyball (BVb) is a highly demanding Olympic sport characterized by intense physical activity and unique environmental challenges, including varying weather conditions and sandy, unstable court surfaces. Despite its popularity, there is a notable lack of scientific research addressing the metabolic and immune responses of elite female athletes in this sport. This study aims to address this gap by investigating two world-class Olympic medalists, female BVb players, who represent a country with a rich history in the sport.